Environmental crises and climate change: Eco-anxiety among young people and the urgent need for a transformative response - Annamaria Lammel (Field Actions Science Reports)
The world faces a threefold environmental crisis: climate change, biodiversity loss, and pollution. Awareness of these crises is growing, as more and more organizations attempt to control harmful human activities. Despite these efforts, the changes made are insufficient. The media delivers alarming news on a daily basis, triggering stress that can turn into eco-anxiety, a chronic fear of environmental catastrophe which in turn can lead to depression and states of anxiety. Climate anxiety, a form of eco-anxiety, is a major threat to mental health in the 21st century. It impacts mental health directly via extreme meteorological events, indirectly via consequences such as famine, and vicariously via the media. Young people are particularly susceptible: 47% of young adults in the US state that it impacts their day-to-day lives. Children are especially vulnerable and may develop eco-anxiety from as young as 8 years old. Tackling this widespread mental health problem, linked to a variety of factors, requires taking action that addresses the root of the problem: education, provision of more green spaces, biophilic design, responsible attitudes, a long-term vision on the part of politicians and businesses, and the transformation of our systems. Governments must protect young people, recognize their fears, and involve them in decision-making. Urgent collective action is essential if we are to protect the mental health of younger generations.